Implementasi Estimasi Biaya (Cloud Architect) Pada Pengembangan Portal Berita Berbasis Website Dengan Menggunakan Bahasa Pemrograman - Mutiar Sukma; Baiq Desthania Prathama (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
PT Chairos International Ventures (CIV) was founded in 2016 as a technology and media company focused on Cloud Computing. Cloud Computing certified independent study and internship activities (MSIB) are carried out online or on-line. The implementation of the independent study program (MSIB) on the independent campus lasted for approximately 5 months. The object of research in this program is to determine cost estimates on a website-based news portal. This type of research is descriptive qualitative research using observation, interview and documentation data collection techniques. The results of this study are a news portal website that can make it easier for people to access and get the latest news.